THE EFFECT OF PERCEIVED VALUE AND CONSUMER INNOVATIVENESS ON PURCHASE DECISIONS MEDIATED BY BRAND IMAGE AT ERHA BEAUTY CLINIC JAMBI - Putri Zulwarni; Ade Octavia; Dahmiri Dahmiri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This resea aims to analyze the effect of perceived value, consumer innovativeness on purchase decisions with Brand Image as a mediating variable. This research is a type of field research with a quantitative approach in the form of associative. The samples are 135 respondents, namely customers who visit Erha Beauty Clinic Jambi. The data used are primary data and secondary data. The analysis uses PLS model by assessing the outer model and inner model. The results conclude that perceived value and consumer innovativeness affect purchase decisions, brand image mediates the relationship between perceived value and purchase decisions, and brand image also mediates the relationship between consumer innovativeness and purchasedecisions.